2017
DOI: 10.1364/ome.7.003815
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-optical and lasing characteristics of Cr^2+-doped CdSe single crystal as tunable coherent source in the mid-infrared

Abstract: We report on a comprehensive characterization of Cr 2+-doped CdSe single crystal as an efficient active material for tunable laser applications in the mid-infrared spectral region. Optical gain, thermo-optical behavior, power efficiency, scalability and wavelength tunability have been thoroughly investigated. Using an antireflection-coated crystal pumped by a Tmfiber laser at at 1.94 μm, 1-W CW output power and 50% slope efficiency at 2.65 μm emission wavelength have been obtained in a diffraction-limited outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The simulation results of the spike pulse duration are illustrated by the solid line, which have the same tendencies as the experimental results. Nevertheless, the calculated values were lower than Value [15,26,34] Refractive index at 2.65 μm, n 2.46…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…The simulation results of the spike pulse duration are illustrated by the solid line, which have the same tendencies as the experimental results. Nevertheless, the calculated values were lower than Value [15,26,34] Refractive index at 2.65 μm, n 2.46…”
mentioning
confidence: 66%
“…Then interest was inspired in the research of this class of materials, and laser oscillations of Cr 2þdoped ZnSe, ZnS, CdSe, CdMnTe, etc., were gradually realized [11][12][13] . Among the materials, Cr 2þ ∶CdSe attracted plenty of attention for its large emission cross section and ultra-broad emission band (2.2-3.6 μm) [14,15] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mid‐IR systems are usually implemented as fibers, [ 4,5 ] as waveguides, [ 6,7 ] or as free‐space optics. [ 8,9 ] For these cases, most of the commonly used mid‐IR transparent materials have a high refractive index: often above 2, and in some cases, up to 4 (see Figure ). High Fresnel loss (also known as surface reflection loss) are associated with a high refractive index, such that the transmittance of normal incident light for materials with a refractive index of 1.6 (sapphire optics) decreases by 95% and to 64% for materials with a refractive index of 4 (germanium optics).…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium Selenide (Space Group: P63mc (186), a=4.30Å, c=7.01Å)) is mainly employed for nuclear radiation detectors operating at room temperature [1], nonlinear optical devices [2] and as substrate for epitaxial growth [3]. Characterization of Cr2+-doped CdSe single crystal showed that it is an efficient active material for tunable laser applications in the mid-infrared spectral region [4] and that Fe2+ : CdSe can be considered a promising medium for amplification of femtosecond pulses in the middle infrared range up to 6 µm [5]. Thermal, mechanical and chemical stability are important properties of this semiconductor which additionally might not suffer from polarization under applied electric fields [6,7].…”
Section: Introductionmentioning
confidence: 99%